Yes because it is a whole number
Answer:
6x^2 -11x -1
Step-by-step explanation:
(3x^2 + 3) - (6x + 4) + (3x^2 - 5x)
Distribute the minus sign
(3x^2 + 3) - 6x - 4) + (3x^2 - 5x)
Combine like terms
3x^2 + 3x^2 - 6x - 5x -4+3
6x^2 -11x -1
So 9:30 17 min goes by so its 9:47 but tim arrived 8 mins before so it was 9:39 when he arrived. Next tyson arrived 20 min after tims ORIGINAL oppt 9:47 20 min 10:07 then for marks 35 min after witch is 10:12
The expression would be 2.98 * 10 to the -7 power? Please tell me if I'm wrong.
<u>Answer:</u> Yes, I can.
Although you haven't asked for the solution, here it is anyway:
2^x = e^(x+2)
x ln(2) = x+2
x ln(2) - x = 2
x [ ln(2) - 1 ] = 2
x = 2 / [ ln(2) - 1 ]
x = 2 / -0.3069... =<u> - 6.518</u>... (rounded)